FAMILY MICROPEZIDAE - Marshall, Stephen; Cardona, Anderson; Wolff, Martha (Zootaxa, 2016)
Sixty species and 14 genera of Micropezidae are recorded from Colombia, including four species of Micropezinae and 56 species of Taeniapterinae. The following species are newly recorded from the country: Grallipeza affinis, G. ecuadoriensis, G. obscura, G. nigrinotata, G. pseudosimplex, Ptilosphen comis, P. conveniens, P. enderleni, P. facetus and P. mimicus.